PERAN KOMPETENSI DAN BUDAYA ORGANISASI DALAM MENINGKATKAN EFEKTIVITAS SUPERVISI MIDDLE MANAGER DI RUMAH SAKIT PENDIDIKAN UNIVERSITAS HASANUDDIN - Askardin, Anna Arnita; Paramita, Rahma; Magfirah, Nurul; Hadianto, Farmady; Kalsum, Ummu; AS, Andi Indahwaty; Arifah, Nur (Jurnal Manajemen Kesehatan Indonesia, 2025)
One of the roles of leaders to improve employee performance is to optimize their role in supervising. This study aims to analyze the effect of competence and organizational culture on the effectiveness of middle manager supervision at Hasanuddin University Teaching Hospital. This study involved 219 employees from 24 installations in the Hasanuddin University Teaching Hospital. Data were analyzed using multiple linear regression using the SPSS application. The results showed that competence (p value = 0.000 < 0.05) and organizational culture (p value = 0.000 < 0.05) influence on the implementation of middle manager supervision at Unhas Teaching Hospital. In conclusion, the competence of middle managers and organizational culture contribute to the implementation of effective supervision.